Design and control of a robotic system with legs, wheels, and a reconfigurable arm. Issue 4 (14th December 2022) - Ye, Linqi; Liu, Houde; Wang, Xueqian; Liang, Bin; Yuan, Bo
Abstract: Unmanned robotic systems are expected to liberate people from heavy, monotonous, and dangerous work. However, it is still difficult for robots to work in complicated environments and handle diverse tasks. To this end, a robotic system with four legs, four wheels, and a reconfigurable arm is designed. Special attention has been given to making the robot compact, agile, and versatile. Firstly, by using separate wheels and legs, it removes the coupling in the traditional wheeled–legged system and guarantees highly efficient locomotion in both the wheeled and legged modes. Secondly, a leg–arm reconfiguration design is adopted to extend the manipulation capability of the system, which not only reduces the total weight but also allows for dexterous manipulation and multi‐limb cooperation. Thirdly, a multi‐task control strategy based on variable configurations is proposed for the system, which greatly enhances the adaptability of the robot to complicated environments. Experimental results are given, which validate the effectiveness of the system in mobility and operation capability.